2002
DOI: 10.1002/cpp.348
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reflection and self‐practice in training of Cognitive Behaviour Therapy: an overview

Abstract: The present paper deals with a developing training element in cognitive behaviour therapy (CBT), the self-practice of therapeutic techniques and the self-exploration of the person of the therapist. Initially, the current status of this training element in CBT is discussed, and a short note on its terminology is presented. Then an overview of the most important objectives of self-practice and self-reflection in CBT, and the concepts and methods of practice of this element is given. The concepts focus on two maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 14 publications
3
50
0
1
Order By: Relevance
“…Fortunately, there is reason to believe that reflection will be beneficial. For instance, Laireiter and Willutzki (2003) reported that applying the Cognitive-Behavioural Therapy (CBT) models and methods to the development of therapists led to self-reported improvements in such areas as empathy. Similarly, Bennett-Levy, Lee, Travers, Pohlman, and Hamernik (2003) studied how 14 CBT practitioners developed as a result of 'co-therapy' sessions, noting benefits in such areas as the therapeutic relationship, empathy, self-reflection and flexibility.…”
Section: Evidence For Ppdmentioning
confidence: 99%
“…Fortunately, there is reason to believe that reflection will be beneficial. For instance, Laireiter and Willutzki (2003) reported that applying the Cognitive-Behavioural Therapy (CBT) models and methods to the development of therapists led to self-reported improvements in such areas as empathy. Similarly, Bennett-Levy, Lee, Travers, Pohlman, and Hamernik (2003) studied how 14 CBT practitioners developed as a result of 'co-therapy' sessions, noting benefits in such areas as the therapeutic relationship, empathy, self-reflection and flexibility.…”
Section: Evidence For Ppdmentioning
confidence: 99%
“…For example, self-assessment was not viewed as robust or accurate enough for summative purposes. Nevertheless, comparing therapists' own ratings of their in-session performance with an assessor's rating provided a useful tool for enhancing self-reflection (Bennett- Levy, 2006;Laireiter & Willutzki, 2003). That being said, participants did not typically employ independent formative and summative assessments, suggesting the need for assessment tools that can serve both functions.…”
Section: Combining Formative and Summative Assessmentsmentioning
confidence: 97%
“…This view is supported by research demonstrating that therapists' self-appraisals typically differ from assessors' appraisals (Brosan, Reynolds, & Moore, 2008;Mathieson, Barnfield, & Beaumont, 2010;McManus et al, 2011). Self-assessment was, however, used to enhance therapists' capacity for self-reflection, a strategy that is supported by an increasing body of literature highlighting self-reflection as an important mechanism for therapist development (Bennett-Levy, 2006;Laireiter & Willutzki, 2003). Participants were aware of the difficulties in using patient outcome data to infer therapists' competence, particularly that it does not take into account treatment-specific factors (i.e., improved outcome may not be due to receiving CBT) and is confounded by patient variables (e.g., patient difficulty and comorbidity).…”
Section: You Can Talk the Talk But Can You Walk The Walk?mentioning
confidence: 97%
“…CBT trainees and clinicians are encouraged to work on their own issues both as an opportunity to genuinely practice the application of cognitive, behavioral and emotive techniques and also to allow them to be better prepared as clinicians to become aware of and handle their thoughts, feelings and behaviors within the therapeutic relationship (Laireiter and Willutzki 2003;Padesky 1996). Practicing techniques on their real problems allows trainees and clinicians to experience them first hand and creates better preparedness for their elegant use with clients.…”
Section: Use Of Personalitymentioning
confidence: 99%